EFFECTIVENESS REDUCING AMMONIA LEVELS FROM WASTE SANGKURIANG CATFISH (Clarias gariepinus) CULTIVATION USING THE PHYTOREMEDIATION METHOD USE WATER HYACINTH (Eichhornia crassipes), Water lettuce (Pistia stratiotes) and Azolla microphylla - Eka Sulistya Ningsih; Nurjannah Nurjannah; Sutaman Sutaman (Universitas Teuku Umar, 2025)
Water quality is a crucial factor in the cultivation of Sangkuriang catfish (Clarias gariepinus). One of the main issues in catfish farming is the increase in ammonia levels in the water, which can negatively impact fish health and the environment. This study aims to analyze the effectiveness of the phytoremediation method using Eichhornia crassipes (water hyacinth), Pistia stratiotes (water lettuce), and Azolla microphylla in reducing ammonia levels from catfish farming wastewater. The research employed an experimental method with a completely randomized design (CRD), consisting of three treatments using each plant type and a control group without treatment. The results showed that the phytoremediation method using water hyacinth was the most effective in reducing ammonia levels, achieving an efficiency of 99.35%. Water lettuce and Azolla microphylla also demonstrated effectiveness in absorbing ammonia, with efficiencies of 98.2% and 96.4%, respectively. Additionally, water quality parameters such as temperature, pH, dissolved oxygen (DO), phosphate, and nitrate were within the optimal range for fish farming. Based on these findings, the phytoremediation method using aquatic plants can be an environmentally friendly solution for managing catfish farming wastewater. Further research is needed to optimize environmental conditions and the number of plants used in the phytoremediation process.